2021
DOI: 10.1002/mbo3.1249
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT‐binding complex mediates azole susceptibility of Aspergillus fumigatus by suppressing SrbA expression and cleavage

Abstract: In fungal pathogens, the transcription factor SrbA (a sterol regulatory element‐binding protein, SREBP) and CBC (CCAAT binding complex) have been reported to regulate azole resistance by competitively binding the TR34 region (34 mer) in the promoter of the drug target gene, erg11A. However, current knowledge about how the SrbA and CBC coordinately mediate erg11A expression remains limited. In this study, we uncovered a novel relationship between HapB (a subunit of CBC) and SrbA in which deletion of hapB signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Then, 100% trichloroacetic acid was added to precipitate the protein after thorough vortexing. After centrifugation at 4°C, the precipitate was collected and then heated at 95°C for 5 min ( 56 , 57 ). Western blotting was then performed to detect the phosphorylation level of MpkA using anti-phospho-ERK1-T202/Y204+ERK2-T185/Y187 (1:2,000, ABclonal Technology Co.) as the primary antibody and anti-rabbit (1:5,000, ABclonal Technology Co.) as the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 100% trichloroacetic acid was added to precipitate the protein after thorough vortexing. After centrifugation at 4°C, the precipitate was collected and then heated at 95°C for 5 min ( 56 , 57 ). Western blotting was then performed to detect the phosphorylation level of MpkA using anti-phospho-ERK1-T202/Y204+ERK2-T185/Y187 (1:2,000, ABclonal Technology Co.) as the primary antibody and anti-rabbit (1:5,000, ABclonal Technology Co.) as the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…In a mouse model, the mitochondrial respiration chain component cycA (cytochrome C gene) and alcC (alcohol dehydrogenase gene) deleted strains have been come out the defect virulence (Grahl et al 2012(Grahl et al , 2011. Chromatin immunoprecipitation followed by parallel DNA sequencing showed that SrbA (sterol regulatory element-binding protein gene) helped regulate ergosterol biosynthesis and iron uptake during hypoxic conditions or iron limitation (Zhang et al 2021a). Critically, the lung is a "sponge," and there are not enough carbon or nitrogen sources on lung surfaces to limit A. fumigatus growth.…”
Section: A Fumigatus Survival Strategies In Hostsmentioning
confidence: 99%